2021
DOI: 10.1101/2021.02.25.432981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calprotectin-mediated zinc chelation inhibitsPseudomonas aeruginosaprotease activity in cystic fibrosis sputum

Abstract: Pseudomonas aeruginosa induces pathways indicative of low zinc availability in the cystic fibrosis (CF) lung environment. To learn more about P. aeruginosa zinc access in CF, we grew P. aeruginosa strain PAO1 directly in expectorated CF sputum. The P. aeruginosa Zur transcriptional repressor controls the response to low intracellular zinc, and we used the NanoString methodology to monitor levels of Zur-regulated transcripts including those encoding a zincophore system, a zinc importer, and paralogs of zinc con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 76 publications
(134 reference statements)
4
9
2
Order By: Relevance
“…The shared response to both Zn limitation and CP treatment was consistent with the known Zn-starvation response and included the downregulation of Zn(II)-containing ribosomal proteins (RpmJ and RpmE) ( Fig 2A, Fig S3 ) and the upregulation of Znu transport proteins (ZnuA, ZnuC), pseudopaline biosynthesis and transport (CntM, CntO) proteins, the Zn(II)-independent ribosomal protein RpmE1, and the Zn(II)-independent paralog to DksA, DksA2 ( Fig 2B, Fig S3 ). Notably, several Zn(II)-dependent proteases (LasA, LasB, ImpA, AprA) were upregulated by both CP and Zn(II) limitation, seemingly contrary to the observed Zn-starvation response and a recent report on decreased protease activity in response to CP (39) ( Fig 2B ). The upregulated proteins that were specific to the Zn-limitation proteome included Zn(II)-independent proteins (CynT2, FolE2) that were not significantly changed in response to CP.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…The shared response to both Zn limitation and CP treatment was consistent with the known Zn-starvation response and included the downregulation of Zn(II)-containing ribosomal proteins (RpmJ and RpmE) ( Fig 2A, Fig S3 ) and the upregulation of Znu transport proteins (ZnuA, ZnuC), pseudopaline biosynthesis and transport (CntM, CntO) proteins, the Zn(II)-independent ribosomal protein RpmE1, and the Zn(II)-independent paralog to DksA, DksA2 ( Fig 2B, Fig S3 ). Notably, several Zn(II)-dependent proteases (LasA, LasB, ImpA, AprA) were upregulated by both CP and Zn(II) limitation, seemingly contrary to the observed Zn-starvation response and a recent report on decreased protease activity in response to CP (39) ( Fig 2B ). The upregulated proteins that were specific to the Zn-limitation proteome included Zn(II)-independent proteins (CynT2, FolE2) that were not significantly changed in response to CP.…”
Section: Resultscontrasting
confidence: 99%
“…Consistent with a recent study (39), CP-treated cells showed a robust Zn-starvation response. This response included increased levels of proteins for Zn(II)-uptake systems, including ZnuACD and proteins for the synthesis and uptake of pseudopaline (CntM and CntO, respectively) (22, 25, 26).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations